Factors Affecting Public Compliance in the Implementation of the Covid-19 Health Protocol - Fauzan Alfikrie; Uti Rusdian Hidayat; Ali Akbar; Nurpratiwi; Mimi Amaludin; Debby Hatmalyakin (School of Nursing, Faculty of Medicine, Lambung Mangkurat University., 2022)
The increase in Covid-19 cases was caused by the lax implementation of the Covid-19 health protocol. The purpose of this study was to identify factors related to community compliance in the application of the COVID-19 health protocol in Kapuas District, Sanggau Regency. This study has used an analytical observational design with a cross-sectional approach. A total of 73 respondents involved in this study were selected by accidental sampling. The results of this study obtained several factors related to compliance in the application of the Covid-19 health protocol, namely income (0.02), perception (0.00), attitude (0.00). Meanwhile, age and knowledge have no relationship with community compliance in implementing health protocols. The public needs to increase awareness by continuing to make efforts to prevent COVID-19 such as using masks, maintaining distance, and always washing hands.